Determinants of Japanese direct investments in selected BIMP-EAGA countries - Kassim bin Hj. Mansor,; Furuoka, Fumitaka *; Lim, Beatrice Fui Yee; Phang, Grace (Sunway University College, 2007)
This paper uses panel data analysis to identify how Japanese multinational corporations (MNCs) allocate their investments in the selected BIMP-EAGA countries (i.e. Malaysia, Indonesia and the Philippines). The paper hypothesizes that the following six elements would influence the inflow of Japanese Direct Investments (JDI) into the area: country?s market size, growth rate of market size, per capita income, trade deficit, inflation rates and political condition. The main findings from the panel data analysis are that there is a significant relationship between Japanese direct investments and political condition in the recipient countries. The inflows of Japanese investment tend to decrease as the political risk increases. It means that Japanese MNCs tend to allocate more investments into the countries with better political condition.